Strength and microstructure properties of spent coffee grounds stabilized with rice husk ash and slag geopolymers. (15th August 2017) - Suksiripattanapong, Cherdsak; Kua, Teck-Ang; Arulrajah, Arul; Maghool, Farshid; Horpibulsuk, Suksun
Highlights: Possibility of using waste materials as recycled pavement construction materials. Explained role of curing time on compressive strength of coffee ground geopolymers. Long term microstructure development was examined via scanning electron microscope. Abstract: This paper investigates the strength and microstructure properties of spent coffee grounds stabilized with rice husk ash and slag geopolymers to produce a green construction subgrade material. Spent coffee grounds (CG) and rice husk ash (RHA) are organic wastes derived from agricultural products. CG is the residue from ground coffee beans. RHA is a by-product from the burning rice husk used to generate electricity. Ground granulated blast furnace slag (S) is a waste by-product derived from steel production. RHA and S were used as geopolymeric precursors (P). This study provides an insight on the long-term strength performance and microstructural formation of geopolymers synthesized from agricultural waste products. The influence factors studied were liquid alkaline activator content (L), RHA content, S content, temperature and curing time. By observing the strength development of CG-RHA geopolymers for up to 90 days, it was found that elevated temperature curing was needed for these CG:RHA geopolymers to develop long-term strengths. Test results show that an optimum mix of CG:RHA:S 70:20:10 cured at 50 °C can achieve an Unconfined Compressive Strength (UCS) of 2 MPa after 90 days of curing. The outcome of this research will enable CG, S and RHA waste products to be used as sustainable materials in pavement applications.